Linking polaron signatures to charge transport in doped thiophene polymers - Abutaha, Anas (2023)
Carrier doping and structural morphology are key knobs to tune thermoelectric transport in conducting polymers. Optical signatures of doping can be correlated to the thermoelectric properties of conducting polymers. In this review, we focus on absorption spectroscopy to understand thermoelectric transport in conducting polymers. Thus, we quantitatively extract the carrier concentration from optical absorption signatures of polarons by linking the absorption ratio of the low-energy polaronic peak (P1) and neutral excitons (π-π*) in doped thiophene-based films with electrical conductivity and Seebeck coefficient using the Boltzmann transport equations (BTE). The rate of change of electrical conductivity with carrier concentration (absorption ratio) differs with variation in doping and/or processing conditions, whereas the Seebeck coefficient decreases monotonically with carrier concentration regardless of doping method as expected. The correlation confirms that charge mobility is the key parameter to improve the TE performance where the method of doping or process conditions creates a wide range of structural disorder controlling the electrical and thermoelectric properties.